Animal and cellular models of atrial fibrillation: a review - Wu, Qiuying; Wu, Xize; Feng, Teng; Chen, Feiyu; Ren, Jiaqi; Gao, Shan; Wang, Bo; Li, Yue; Gong, Lihong (Frontiers in cardiovascular medicine, 2025)
Modeling atrial fibrillation (AF) is crucial for investigating its pathogenesis and developing new therapeutic strategies. To better explore the mechanisms underlying AF and promote the progress of basic research, it is particularly important to develop accurate animal models that closely simulate the progression of clinical disease. This review summarizes the methods and evaluation criteria for establishing animal and cellular AF models over the past decade, highlighting the advantages and limitations of various models to provide a reference for basic research and treatment of AF. Current experimental animals are primarily categorized into small animals (mice, rats, rabbits), large animals (dogs, pigs, sheep, horses), and model organisms (zebrafish), with modeling methods including electrophysiological induction, chemical induction, trauma induction, and genetic editing. Cellular models commonly use primary cultured cardiomyocytes, the HL-1 cell line, hiPSC-CMs, and H9c2 cells as subjects of study. However, due to the lack of standardized modeling protocols, researchers evaluate AF models based on electrophysiological properties, atrial functional metrics, and biomarkers. Three-dimensional engineered tissues and artificial intelligence, as emerging fields, play an important role in the diagnosis, treatment, and prognostic monitoring of AF. This paper not only summarizes the current progress in AF model research but also points out the deficiencies of existing models, offering guidance for future research directions.